Yhteensovittavan johtamisen käsite sosiaali- ja terveydenhuollon kontekstissa - Ulla Kekäläinen; Sanna Tchaplinski; Johanna Lammintakanen; Sanna Laulainen (Focus Localis, 2026)
The need for Integrative leadership is currently emphasized, especially in health and social care where health and social services are being integrated into client-oriented entities. The article describes and analyses the concept of integrative leadership by applying the three-phase hybrid conceptual analysis model proposed by Schwartz-Barcott and Kim (2000). In the theoretical phase of the study, the characteristics of integrative leadership were identified through an integrative literature review (N=14). In the empirical phase characteristics were examined in the context of health and social care management based on individual interviews of social care managers (n=37). In the analytical phase, the results were combined. Four characteristics were identified for the concept of integrative leadership, namely holistic, networked, connectiveness and purposefulness. In addition, based on the analytical stage, a more precise definition of the concept of integrative leadership is proposed.